The Influence of Corporate Social Responsibility on Financial Performance with Good Corporate Governance as Moderating Variable - Narwastu, Narwastu; Rusli, Devvy (SAN Scientific, 2023)
This study aims to determine the effect of Corporate Social Responsibility on financial performance moderated by Good Corporate Governance in construction and building sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The quantitative methodology was used in this study. Construction and building companies listed on the Indonesia Stock Exchange for 2019 through 2021 comprise this study's population. Purposive sampling was used for the study's sampling, which produced final sample of 13 businesses. The information used in this study is secondary data. The results of this study indicate that: (1) economic dimension information has a significant positive effect on financial performance, (2) environmental dimension information has significant negative effect on financial performance, (3) social dimension information has insignificant negative effect on financial performance, (4) GCG can moderate the relationship of information on the environmental dimension to financial performance (5) GCG cannot moderate the relationship between information on the economic dimension and information on the social dimension on financial performance. In increasing firm value, research implications for companies should always be consistent in disclosing CSR information and the implementation of GCG to avoid problems that can lower the image company in the eyes of investors and the public.